Pengaruh Cukai Hasil Tembakau, Pendapatan Per Kapita, Produksi Tembakau, dan Konsumsi Rokok Terhadap Pajak Rokok di 15 Provinsi Produsen Tembakau Terbesar di Indonesia Tahun 2016-2019 - Anggraeni, Wahyu; Bieattant, Licke (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Cigarette consumption in Indonesia is increasing every year. In 2018, national cigarette consumption was the highest in the ASEAN region. In 2019, it reached 82.78 (83) cigarettes per week. Even during 2017-2019, expenditure on cigarette consumption was greater than expenditure on rice consumption. However, the steps taken by the Indonesian government such as adjusting the tobacco product excise (CHT) tariff and setting a cigarette tax of 10% of the excise have not been able to reduce cigarette consumption in the country. This study aims to analyze the effect of tobacco product excise (CHT), per capita income, tobacco production, and cigarette consumption on cigarette taxes in the 15 largest tobacco producing provinces in Indonesia in 2016-2019. This study used secondary data obtained from various related agencies and methods of Random Effect Model (REM) or Estimated Generalized Least Square (EGLS). The results showed that the tobacco production variable had a positive and significant effect on cigarette taxes. Meanwhile, tobacco product excise (CHT), income per capita, and cigarette consumption had a positive and insignificant effect on cigarette taxes. Based on the F test, all independent variables in this study simultaneously had a significant effect on cigarette taxes. R- squared value of 0.267094 means that 26.7% of the models in this study can be explained by independent variables, while the remaining 73.3% are explained by other variables outside of thisstudy.